TREND NIKAH DI KUA TANPA WALIMAH DALAM PERSPEKTIF ‘URF (STUDI KASUS DI KECAMATAN PENANGGALAN) - Agustina Berutu; Sudirman Suparmin (Raudhah - Proud To Be Professional, 2023)
Abstract This research aims to find out how the trend of meriage without walimah, walimah and the law of carrying it out, ‘urf and its position,how the custom of the community in penanggalan sub-district in the marriage process, and walimah in the perspective of ‘urf and culture. This research is included in the qualilative approach research, namely qualitative research using descriptive da in the form of written or spoken words from people. And also using library research that collects data from books,journals, and sources relevan to this research.